2011
DOI: 10.1002/hipo.20995
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal lesions can enhance discrimination learning despite normal sensitivity to interference from incidental information

Abstract: Spatial properties of stimuli are sometimes encoded even when incidental to the demands of a particular learning task. Incidental encoding of spatial information may interfere with learning by (i) causing a failure to generalize learning between trials in which a cue is presented in different spatial locations and (ii) adding common spatial features to stimuli that predict different outcomes. Hippocampal lesions have been found to facilitate acquisition of certain tasks. This facilitation may occur because hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…previously, this supports the view that in intact animals, separate memory systems can compete for control over the navigating animal's behaviour [53][54][55]. In line with the current results, previous work has shown that hippocampal lesions facilitate 'response' strategies, such as our landmark discrimination, when the use of extra-maze cues provide a parallel solution [42,[56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…previously, this supports the view that in intact animals, separate memory systems can compete for control over the navigating animal's behaviour [53][54][55]. In line with the current results, previous work has shown that hippocampal lesions facilitate 'response' strategies, such as our landmark discrimination, when the use of extra-maze cues provide a parallel solution [42,[56][57][58].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, to discriminate between the two stimuli, the rats could either identify the actual location of the CS within the chamber, in a hippocampal‐dependent manner, or simply identify whether the CS was on the left or right of their visual field. The latter strategy is both more efficient and hippocampal‐independent, so elimination of competition from slower hippocampal‐dependent processes can actually facilitate performance of such a task (Sanderson et al, ). The PCA procedure in the present study did not involve discrimination and would therefore not be expected to improve in this manner with hippocampal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal damage sometimes results in better performance on similar tasks and this outcome is often attributed to a reduction of interference (Han et al, 1998; Saksida et al, 2007; Sanderson et al, 2011). In the present study, however, performance on the FPFN task was enhanced even when inter-trial intervals were substantially increased.…”
Section: Discussionmentioning
confidence: 99%